Modelling plant water use of the grassland and thicket biomes in the Eastern Cape, South Africa: towards an improved understanding of the impact of invasive alien plants on soil chemistry, biomass production and evapotranspiration - Gwate, Onalenna (Rhodes University, Faculty of Science, Institute for Water Research, 2018)
It is imperative to understand the strong coupling between the carbon capture process and water use to sustainably manage rangelands. Woody encroachment is undermining rangelands grass production. Evapotranspiration (ET) highlights the links between ecosystem carbon capture process and water use. It forms the biggest flux of the hydrological cycle after precipitation yet it is not well understood. The Grassland and the Albany Thicket (AT) biomes in the Eastern Cape, South Africa, provide an interesting space to study the dynamics in rangelands biomass production and the associated water use. Therefore, the main purpose of this study was to contribute towards management of rangelands by understanding the dynamics in rangeland grass production and water use. To achieve this aim, the impact of Acacia mearnsii, an invasive alien plant, on soil chemical properties and rangelands grass production was investigated. This was achieved by analysing the biophysical attributes of A. mearnsii as they related to grass production. Secondly, selected soil variables that could be used as a prognosis for landscape recovery or deterioration were evaluated. In addition, aboveground grass biomass was measured in areas cleared of A. mearnsii and regression equations were prepared to help model aboveground grass biomass in areas cleared of A. mearnsi. The thesis also explored dynamics in water vapour and energy fluxes in these two biomes using an eddy covariance system. Consequently, water vapour and energy fluxes were evaluated in order to understand landscape water use and energy partitioning in the landscape. The study also tested the application of Penman-Monteith equation based algorithms for estimating ET with micrometeorological techniques used for validation. Pursuant to this, the Penman- Monteith-Leuning (PML) and Penman-Monteith-Palmer (PMP) equations were applied. In addition, some effort was devoted to improving the estimates of ET from the PMP by incorporating a direct soil evaporation component. Finally, the influence of local changes in catchment characteristics on ET was explored through the application of a variant of the Budyko framework and investigating dynamics in the evaporative index as well as applying tests for trends and shifts on ET and rainfall data to detect changes in mean quaternary catchment rainfall and ET. Results revealed that A. mearnsii affected soil chemical properties and impaired grass production in rangelands. Hence, thinning of canopies provided an optimal solution for enhanced landscape water use to sequestrate carbon, provide shade, grazing, and also wood fuel. It was also shown that across sites, ET was water limited since differences between reference ET and actual ET were large. ET was largely sensitive to vapour pressure deficit and surface conductance than to net radiation, indicating that the canopies were strongly coupled with the boundary layer. Rangeland ET was successfully simulated and evaporation from the soil was the dominant flux, hence there is scope for reducing the so-called 'unproductive' water use. Further, it was shown that the PML was better able to simulate ET compared to the PMP model as revealed by different model evaluation metrics such as the root mean square error, absolute mean square error and the root mean square observations standard deviation ratio. The incorporation of a soil evaporation component in the PMP model improved estimates of ET as revealed by the root mean square error. The results also indicated that both the catchment parameter (w) and the evaporative index were important in highlighting the impacts of land cover change on ET. It was also shown that, despite changes in the local environment such as catchment characteristics, global forces also affected ET at a local scale. Overall, the study demonstrated that combining remote sensing and ground based observations was important to better understand rangeland grass production and water use dynamics.
Keywords: Grasslands -- South Africa -- Eastern Cape; Invasive plants -- South Africa -- Eastern Cape; Rangelands -- South Africa -- Eastern Cape; Range ecology-- -- South Africa -- Eastern Cape; Rangelands -- Water-supply; Rangelands -- Weed control; Evapotranspiration; Plant-water relationships